Disaster Management Policy Implementation Model In Sigi-Indonesia - Riadi, Slamet; Rifgal, Moh; Waris, Irwan (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This study aims to determine the implementation model of disaster management policies in Sigi Regency, Central Sulawesi, which is focused on the rehabilitation and reconstruction phase of the earthquake and liquefaction disaster, namely the provision of assistance for community housing repairs (stimulants) and assistance for the construction of permanent residences (permanent housing) which are the responsibility of the community. responsible for the National Disaster Management Agency for Sigi Regency. The method used is a qualitative method, data collection techniques with observation, interviews, and documentation. The researcher conducted interviews with 10 (ten) informants consisting of program implementers and program recipients with questions related to 4 (four) aspects of Thomas B. Smith's policy implementation model. The results showed that the ideal aspects of the policy were implemented well. The relationship between the implementing organization (BPBD) and the target group brings the desired results. Socialization takes place at all levels and involves many people. As for the aspect of the target group, due to the lack of support for the target group, the construction of houses was not completed according to schedule, and there were no regulations for house construction activities. Based on observations, implementing organizations are ineffective due to lack of resources which results in program delays. The emphasis on environmental variables in this study is how external factors such as social, economic, and political situations can influence the implementation of disaster management policy models in Sigi Regency.